Analisis Yuridis terhadap Pengambilan Data Pribadi Pemilih Tanpa Izin oleh Partai Politik untuk Pemilu - Zidane Fairuz Drajat; Sanusi; Ari Nurhaqi (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the legal protection and legal consequences of the practice of collecting voter personal data without permission by political parties in the political party information system (SIPOL). This study uses a normative legal approach using primary, secondary and tertiary legal materials. The results of the study found that the practice of collecting personal data without permission is rooted in the fragility of the verification mechanism in the Political Party Information System (SIPOL) which has not integrated comprehensive personal data protection standards as mandated by Law Number 27 of 2022 concerning Personal Data Protection. In addition to violating privacy. This data collection has an impact on hindering careers in the public sector such as civil servants, the TNI, the Polri and election organizers due to the forced loss of political independence status. Therefore, strengthening regulations, political party membership verification mechanisms and effective law enforcement are necessary to guarantee personal data protection and legal certainty for the public.